We start with the following integral


which is easily evaluated to ${\frac {{a}^{-\lambda+1}}{\lambda-1}}$ by direct integration over $\alpha$ assuming that $a>0,\lambda>1$. This is not what I want to do. In my real-world case the situation is more complicated: I have multiple integrals over $\alpha_1,\ldots,\alpha_n$ from $0$ to $\infty$, and the integrand is $(f(\alpha_1,\ldots,\alpha_n))^{-\lambda}$ where $f$ is a polynom of degree $n$ of $\alpha_1,\ldots,\alpha_n$. Though the problem I stumbled upon occurs in the simplified integral $I$:

Given the Mellin-Barnes representation

$$ \frac{1}{(a+b)^\lambda} = \frac{1}{\Gamma(\lambda)}\frac{1}{2\pi i} \int_{c-i\infty}^{c+i\infty} \mathrm{d}z\,\Gamma(-z)\Gamma(\lambda+z)\frac{a^z}{b^{\lambda+z}}$$

(The contour is closed such that poles of $\Gamma(-z)$ are separated from those of $\Gamma(\lambda+z)$; the residues will give a geometric series that leads to the representation.)

I can apply it to the integrand of $I$:

$$I=\int_0^\infty\mathrm{d}\alpha\,(a+\alpha)^{-\lambda}=\frac{1}{\Gamma(\lambda)}\frac{1}{2\pi i}\int_0^\infty\mathrm{d}\alpha \int_{c-i\infty}^{c+i\infty} \mathrm{d}z\,\Gamma(-z)\Gamma(\lambda+z)\frac{a^z}{\alpha^{\lambda+z}}$$

My plan was now to integrate over $\alpha$, since the sum in the denominator was converted to a product, and the $\alpha$-integration should be trivial. The problem here is that the integration is from $0$ to $\infty$ and the integration over $\alpha$ is not possible here.

Can someone point me to the source of the problem in this situation?

For those familiar with physics: $\alpha$ is a Schwinger parameter coming from parametrizing a Feynman loop integral (https://en.wikipedia.org/wiki/Schwinger_parametrization). One usually performs Feynman-parametrization (https://en.wikipedia.org/wiki/Feynman_parametrization), which leads to integrals from $0$ to $1$ with integrands similar to $I$. Then one inserts the Mellin-Barnes representation and can perform the outer integrations trivially. Only the Mellin-Barnes integrals are left to perform. In my case it is a bit more complicated and I cannot use Feynman parametrization.

EDIT Addition: Stumbling upon the mellin transformation representation of exp(-y) I noticed the same problem here:

$$\int_0^\infty \mathrm{d}y\, e^{-y} = 1 = \frac{1}{2\pi i}\int_0^\infty \mathrm{d}y\int_{c-i\infty}^{c+i\infty}\mathrm{d}s\, \Gamma(s) y^{-s}$$


The problem lies with the Mellin-Barnes representation $$ \frac{1}{(a+b)^\lambda} = \frac{1}{\Gamma(\lambda)}\frac{1}{2\pi i} \int_{c-i\infty}^{c+i\infty} \mathrm{d}z\,\Gamma(-z)\Gamma(\lambda+z)\frac{a^z}{b^{\lambda+z}} $$ You can close the contour either to the right or to the left, depending on whether a is larger or smaller than b. However, when you are integrating over $\alpha$, in one part it is smaller than a and in the other part larger, so there's no way to close the contour that would be always valid. What you can do is split the integration over $\alpha$ in two parts, and exchange the roles of a and b in each part, viz. $$ \int_0^\infty \frac{1}{(a+\alpha)^\lambda} \mathrm{d} \alpha = \int_0^a \frac{1}{\Gamma(\lambda)}\frac{1}{2\pi i} \int_{-i\infty}^{i\infty} \mathrm{d}z\,\Gamma(-z)\Gamma(\lambda+z)\frac{\alpha^z}{a^{\lambda+z}} \mathrm{d} \alpha \\+ \int_a^\infty \frac{1}{\Gamma(\lambda)}\frac{1}{2\pi i} \int_{c-i\infty}^{c+i\infty} \mathrm{d}z\,\Gamma(-z)\Gamma(\lambda+z)\frac{a^z}{\alpha^{\lambda+z}} \mathrm{d} \alpha $$ This is then convergent for $a>0, \lambda > 1$ (taking e.g. $c=\lambda/2$), and you can interchange the $\alpha$ and the $z$ integration.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.